Influence of stress field anisotropy on drilling-induced tensile fracture. Issue 5 (17th October 2018) - Hu, Manman; Veveakis, Manolis; Regenauer-Lieb, Klaus
Abstract : Drilling-induced tensile fracture under anisotropic stress conditions is investigated numerically with an elasto-viscoplastic constitutive model, in which the plastic strain rate can be decomposed into deviatoric and volumetric components. Both the deviatoric and volumetric invariants of the plastic strain rate are assumed to follow an incremental power-law relationship with an Arrhenius dependence. Thermal equilibrium is incorporated into the system, which extends the conventional understanding of stress-induced tensile fracture into an energy-based problem. The rock around the borehole is modelled as impermeable and pressure insensitive (i.e. von Mises material) for simplicity. Anisotropic borehole scenarios characterised by various stress anisotropy ratios are investigated with a focus on the distribution of circumferential stress and its evolution. Simulation results have demonstrated that stress field anisotropy fundamentally promotes shear banding and hence borehole instability.